Fungemia in Tertiary Hospitals; An Overview Fungal Profile, Antifungal Resistance, and Antifungal Therapy - Monita, Syafira Putri; Endraswari , Pepy Dwi; Bramantono; Asmarawati , Tri Pudy; Khanfar, Sarah Amjad Abdel-Raouf (Indonesian Journal of Tropical and Infectious Disease, 2025)
Fungemia is a bloodstream infection caused by fungal pathogen and commonly occurs in hospitalized patients with certain risk factors. Indonesia itself is a tropical country with middle income that makes the incidence rate of fungemia tend to be higher, namely10/1 0,000 people. A recent study about candidemia conducted in Dr. Soetomo General Academic Hospital stated that the most common species that caused candidemia is Candida albicans (33.96%) and the blood sample mostly collected from patients from high care unit and patient with diabetes. We conducted this study to provide a new overview of data on the profile of the causes of fungal infections, patterns of fungal resistance to antifungals, and antifungal therapy in patients with fungemia in hospitalized patients at Dr. Soetomo General Academic Hospital, Surabaya, for the period of January December 2023. This research is a descriptive study using the patient’s medical records. Variables observed in this study include; gender, age, care unit, risk factor, species distribution, resistance pattern, type of antifungal therapy, and duration of antifungal therapy. Mostly the blood cultures are collected from female patients aged 0-9 years old. This study also found that most blood cultures are collected from patients in intensive care unit with use of CVC. Most of the patients did not receive antifungal therapy The most frequent found species is Candida parapsilosis with highest resistance rate found in Amphotericin-B. The most common antifungal that is used is Fluconazole which is mostly given within the range of 8-14 days .